2022
DOI: 10.3390/ijms232415661
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of AMT2-Type Ammonium Transporters Reveal That CsAMT2.2 and CsAMT2.3 Potentially Regulate NH4+ Absorption among Three Different Cultivars of Camellia sinensis

Abstract: Ammonium (NH4+), as a major inorganic source of nitrogen (N) for tea plant growth, is transported and distributed across membranes by the proteins of ammonium transporters (AMTs). However, the AMT2-type AMTs from tea plants remain poorly understood. In this study, five CsAMT2 subfamily genes were identified in tea plant genomes, and their full-length coding sequences (CDS) were isolated from roots. Then, a NH4+ uptake kinetic comparison of Fudingdabaicha (FD), Huangdan (HD), and Maoxie (MX) showed that FD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Interestingly, we found that AMT2, encoding a high-affinity ammonium transporter, is a potential target gene of miR6155. In previous studies, it has been shown that AMT2 potentially regulates ammonium uptake in different plants (Zhang et al, 2022). Additionally, Giehl et al has shown that AMT2;1 was crucial for root-to-shoot translocation of ammonium in Arabidopsis (Giehl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that AMT2, encoding a high-affinity ammonium transporter, is a potential target gene of miR6155. In previous studies, it has been shown that AMT2 potentially regulates ammonium uptake in different plants (Zhang et al, 2022). Additionally, Giehl et al has shown that AMT2;1 was crucial for root-to-shoot translocation of ammonium in Arabidopsis (Giehl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Specific primers (Supplementary Table 3 ) for the CCoAOMT genes were designed by Primer Premier 5.0 software. The CsGAPDH1 (KA295375.1)was selected as the internal reference gene for the detection of gene expression [ 52 ]. Each 10 µL reaction contained 5 µL of 2×PerfectStart Green qPCR SuperMix, 0.5 µL of forward primer, 0.5 µL of reverse primer, 1 µL of cDNA, and 3 µL of RNase-free water.…”
Section: Methodsmentioning
confidence: 99%
“…Their results suggested that the differences in these indicators varied in the five cultivars tested as the N concentration increased and membership function could be used to evaluated the NUE of each cultivar synthetically. Also, CsAMTs expression profiles in response to NH 4 + differed among cultivars ( Zhang et al., 2018 ; Zhang et al., 2022b ). Still, it was possible to detect that CsNRT2 participated in NO 3 − transport under low N conditions ( Hu et al., 2023 ; Lin et al., 2023b ).…”
Section: An Overview Of Nitrogen Use Efficiency Assessment By Tea Plantsmentioning
confidence: 99%
“…CsAMT1.1 and CsAMT1.5 expression levels were significantly higher in the roots of the FuDingDaBaiCha cultivar than Longjin43 cultivar ( Zhang et al., 2022a ). After NH 4 + resupply, CsAMT1.2 , CsAMT2.2 , and CsAMT2.3 genes were differentially induced in tea cultivars with different NH 4 + -uptake efficiency, indicating the uneven NH 4 + transport capacity among cultivars ( Zhang et al., 2018 ; Zhang et al., 2022b ).…”
Section: Nitrogen Transport In Plantsmentioning
confidence: 99%
See 1 more Smart Citation